Mopsa-C: Modular Domains and Relational Abstract Interpretation for C Programs (Competition Contribution) - Monat, Raphaël; Ouadjaout, Abdelraouf; Miné, Antoine (Tools and Algorithms for the Construction and Analysis of Systems, 2023)
Mopsa is a multilanguage static analysis platform relying on abstract interpretation. It is able to analyze C, Python, and programs mixing these two languages; we focus on the C analysis here. It provides a novel way to combine abstract domains, in order to offer extensibility and cooperation between them, which is especially beneficial when relational numerical domains are used. The analyses are currently flow-sensitive and fully context-sensitive. We focus only on proving programs to be correct, as our analyses are designed to be sound and terminating but not complete. We present our first participation to SV-Comp, where Mopsa earned a bronze medal in the SoftwareSystems category.